Effects of increasing dietary dried distillers grains with solubles and glycerol on pork loin quality - Gipe, A.N.; Houser, Terry A.; Duttlinger, A.W.; Tokach, Michael D.; Dritz, Steven S.; Nelssen, Jim L.; Prusa, K.J.; Fedler, C.A.; DeRouchey, Joel M.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,160 barrows (PIC, initially 68.4 lb) were used in a 70-d study to determine the influence of dried distillers grains with solubles (DDGS) and glycerol on pork loin quality attributes. The pigs were blocked by weight and randomly assigned to 1 of 6 dietary treatments with 7 replications per treatment. Pigs were fed corn-soybean meal-based diets with the addition of DDGS, glycerol, or a combination of these. The treatments were arranged in a 2 × 3 factorial with main effects of DDGS (0 or 20%) and glycerol (0, 2.5, or 5%). Pork loins from the 2 heaviest barrows from each pen were utilized for analysis. There were no DDGS × glycerol interac-tions for purge loss, instrumental color (L*a*b*), visual color, marbling score, drip loss, visual color, pH, Warner-Bratzler shear force (WBSF), cook loss, and most sensory characteristics. However, there was a DDGS × glycerol interaction (P < 0.03) for off-flavor intensity. Specifically, pigs fed 20% DDGS without added glycerol had more off-flavors than pigs fed any other treatment. Pigs fed diets with added DDGS had higher WBSF values, lower myofibrillar tenderness, lower overall tenderness scores, lower connective tissue scores, and more off-flavors (P < 0.04) than pigs fed diets with no DDGS. In conclusion, feeding pigs 20% DDGS resulted in less tender chops with more off-flavors. Yet, the inclusion of glycerol in the diet decreased the intensity of off-flavors in pork chops.
Keywords: Dried distillers grains with solubles; Glycerol; Off-flavor; Pork quality; tenderness